Історіографія участі Державної прикордонної служби України в російсько-українській війні (2014–2018 рр.) - Ананьїн, Олег (Київський національний університет імені Тараса Шевченка, 2024)
У статті здійснено узагальнення історіографії участі Державної прикордонної служби України в російсько-українській війні в період 2014–2018 рр. Розглянуто перебіг активних бойових дій за контроль над державним кордоном та участь прикордонних підрозділів в охороні смуги безпеки вздовж лінії розмежування.

The article summarizes the historiography on the topic of the study on the participation of the State Border Guard Service of Ukraine in the Russian-Ukrainian war in 2014–2018. It covers direct combat operations as well as control measures on the demarcation line in certain areas of Donetsk and Luhansk regions and civil-military cooperation in liberated territories.
Historiography of the Participation of the State Border Guard Service of Ukraine in the Russian-Ukrainian war (2014–2018)
Keywords: історіографія; російсько-українська війна; гібридна війна; протидія агресії; історія державного кордону; захист (охорона) державного кордону; антитерористична операція; Державна прикордонна служба України; historiography; Russian-Ukrainian war; hybrid war; countering aggression; history of the state border; protection (defense) of the state border; anti-terrorist operation; State Border Guard Service of Ukraine